STUDY OF WEED MANAGEMENT PRACTICES ON GROWTH, ROOT NODULATION AND YIELD COMPONENTS OF VEGETABLE COWPEA [VIGNA UNGUICULATA (L.) WALP.] - DINESH SAH; R. K. DUBEY; V. SINGH; P. DEBNATH (The Bioscan, 2015)
An experiment was conducted to examine the effect of various weed control practices on growth, nodulation and pod yield of vegetable cowpea during post monsoon season of 2013. The treatments comprised of T1: Weedy check, T2: Weed free, T3: Pendimethalin 30EC @ 1kg ai./ha, T4: Pendimethalin 30EC @ 1kg ai./ha + one hand weeding, T5: Quizalofop-ethyl 5EC @ 0.05kg ai/ ha, T6: Quizalofop-ethyl 5EC @ 0.05kg ai/ha + one hand weeding, T7: Black polyethylene mulch and T8: Slashed grass mulch, which were laid out in Randomized Complete Block Design with four replications. Significant variations for weed population and dry matter accumulation, crop growth parameters and yield attributing traits were observed under influence of different weed control measures. Lowest number of weeds and weed dry weight as well second highest WCE (99.1%) were recorded with polyethylene mulch (T7) followed by quizalofop-ethyl @ 0.05 kg ai/ha + 1 HW(T6), whereas, in weed free plot no any weeds were recorded and expressed 100% WCE. Highest value of growth, yield attributes and pod yield (9.29 t/ha) recorded in plot treated with slashed grass mulch (T8). It was observed that presence of weeds caused approximate 35.60% reductions in pod yield in comparison to weed free situation.